A Novel SNP in the Promoter Region of IGF1 Associated With Yunshang Black Goat Kidding Number via Promoting Transcription Activity by SP1 - Li, Kunyu; Liu, Yufang; He, Xiaoyun; Tao, Lin; Jiang, Yanting; Lan, Rong; Hong, Qionghua; Chu, Mingxing (Frontiers in Cell and Developmental Biology, 2022)
IGF1, a member of the insulin-like growth factor (IGF) superfamily, is also known as growth-promoting factor (somatomedin C). IGF1 is involved in vertebrate growth and development, body immunity, cell metabolism, reproduction and breeding. However, there are relatively few studies on the relationship between IGF1 and goat reproduction. In this study, a new transcription factor SP1 binding to the IGF1 g. 64943050T>C promoted granulosa cells (GCs) proliferation. A mutation g.64943050T>C located in the promoter region of the IGF1 was identified. Association analysis revealed that the kidding number in the first, second litters and the average number of first three litters of CC genotype (2.206±0.044, 2.254±0.056 and 2.251±0.031) was significantly higher than that in TC genotype (1.832±0.049, 1.982±0.06 and 1.921±0.034) and TT genotype (1.860±0.090, 1.968±0.117 and 1.924±0.062) (P<0.05). The kidding number in the third litter of CC genotype (2.355±0.057) was significantly higher than that in TT genotype (2.000±0.107) (P<0.05). Then, the function of this mutation was validated by dual-luciferase report assay and EMSA. The results showed that the luciferase activity of IGF1-Mutant-C was significantly higher than that in IGF1-Wild-T (P<0.05). The EMSA also showed the binding ability of IGF1-Mutant-C was higher than that in IGF1-Wild-T (P<0.05). Subsequently, the transcription factor SP1 was predicted binding to the mutation of IGF1 (g.64943050T>C). Overexpression of SP1 promotes the expression of IGF1 in the primary granulosa cells (GCs). The results of CCK-8 assay and the expression of GCs proliferation factors (CDK4, Cyclin-D1 and Cyclin-D2) demonstrated that SP1 promoted GCs proliferation by regulates IGF1 expression. Our results suggested that the IGF1 g.64943050T>C significant associated with the kidding number of Yunshang black goat, and SP1 as a transcription factor of IGF1 binding to the mutation T>C regulated the expression of IGF1. Furthermore, SP1 promoted the goat GCs proliferation by regulating the expression of IGF1, which provide a new insight for the goat fertility trait.